Democratic beginnings : founding the Western States - Bridges, Amy (University Press of Kansas, 2015)
State constitutions are blueprints for government institutions, declarations of collective identity, statements of principle, values, and goals. It naturally follows, and this book demonstrates, that the founding documents and the conventions that produced them reflect the emerging dynamics of American democracy in the nineteenth century. Nowhere is this more clear, Amy Bridges tells us in Democratic Beginnings, than in the American West. A close study of the constitutional conventions that founded eleven Western states, and of the constitutions they wrote, Democratic Beginnings traces the arc.